Dashboard development for near real-time visualization of COVID-19 vaccine safety surveillance data in the Vaccine Safety Datalink. Issue 22 (11th May 2022) - Kenigsberg, Tat'Yana A.; Hause, Anne M.; McNeil, Michael M.; Nelson, Jennifer C.; Ann Shoup, Jo; Goddard, Kristin; Lou, Yingbo; Hanson, Kayla E.; Glenn, Sungching C.; Weintraub, Eric S.
Highlights: The Vaccine Safety Datalink created a COVID-19 vaccine dashboard to facilitate timely analysis and effective dissemination of vaccine safety results. Abstract: The Vaccine Safety Datalink (VSD) conducts active surveillance and vaccine safety research studies. Since the start of the U.S. COVID-19 vaccination program, the VSD has conducted near real-time safety surveillance of COVID-19 vaccines using Rapid Cycle Analysis. VSD investigators developed an internal dashboard to facilitate visualization and rapid reviews of large weekly automated vaccine safety surveillance data. Dashboard development and maintenance was informed by vaccine surveillance data users and vaccine safety partners. Key metrics include population demographics, vaccine uptake, pre-specified safety outcomes, sequential analyses results, and descriptive data on potential vaccine safety signals. Dashboard visualizations are used to provide situational awareness on dynamic vaccination coverage and the status of multiple safety analyses conducted among the VSD population. This report describes the development and implementation of the internal VSD COVID-19 Vaccine Dashboard, including metrics used to develop the dashboard, which may have application across various other public health settings.